Finding alternative community-based learning delivery for parenting skills during COVID-19 for mothers with children aged 0–3 Years - Pandia, Weny Savitry S.; Suwartono, Christiany; Hestyanti, Yohana Ratrin; Tanuwijaya, Kartika Anggita; Abraham, Natasha Sheir; Henry, Eddy; Herarti, Fitriana; Irwanto, (Frontiers in Education, 2024)
Parenting training has been considered crucial to improving child development. The Tanoto Foundation's parenting program intervention was started in 2021 when the COVID-19 pandemic impacted government policies in Indonesia. Preventive measures that limit mobility affect the sustainability of face-to-face parenting interventions. The study aimed to explore alternative intervention methods, such as face-to-face, blended, online with facilitators, and self-learning, for parenting skills learning during emergencies. A 1-year non-randomized quasi-field experiment using a mixed quantitative-qualitative approach was conducted to 762 participants. SIGAP Q, the HOME Inventory, and CREDI were used for quantitative measurements, while interviews and focused group discussions (FGDs) provided qualitative data. The quantitative data were analyzed using multiway ANOVA, and the qualitative data were analyzed using thematic analysis. The study found that all intervention modalities delivered positive outcomes. In contrast, face-to-face delivered the largest gain, followed by online with facilitators, blended learning, and online self-learning (a web-based learning management system). As an alternative, online with facilitators is the best for delivering parenting materials, followed by online self-learning (independent) modes of intervention. Blended and online models provide alternative models in emergency contexts. Implications are discussed in this article.